The Application Of The Rough Set Method To Analyze The Contribution Of Management Of Science Laboratory Use To Students' Science Process Skills - Wahyudi Sihombing, Ridho; Rian Putra, Randi; Nasution, Darmeli (Cattleya Darmaya Fortuna, 2024)
The development of Information Technology is currently experiencing very rapid progress. Many agencies, both government and private, are trying to improve the efficiency and effectiveness of their work through the implementation of computerized information systems. At PT. Primajaya Multi Technology to support the company's performance, an inventory of goods is needed to be used in work such as office supplies, laptops/PCs, printers, and so on. From the author's observations, the inventory of goods does not yet have a computerized system, but inventory data processing is still done manually. in the process of designing the system using the Unified Modeling Language (UML). As the author has explained above, the purpose of making this journal is to build a laptop inventory application system that will be run by admin staff to facilitate the recording of laptop inventory items.